Botulinum Toxin for Pain Relief in Cancer Patients: A Systematic Review of Randomized Controlled Trials - Lorenzo Lippi; Alessandro de Sire; Alessio Turco; Martina Ferrillo; Serdar Kesikburun; Alessio Baricich; Stefano Carda; Marco Invernizzi (Toxins, 2024)
Cancer pain is one of the most disabling symptoms complained by cancer patients, with a crucial impact on physical and psychological well-being. Botulinum neurotoxins (BoNTs) type A and B have emerged as potential interventions for chronic pain; however, their role in these patients is still debated. Thus, this systematic review of randomized controlled trials aimed at assessing the effects of BoNT treatment for cancer pain to guide physicians in an evidence-based approach integrating BoNT in cancer care. Out of 5824 records, 10 RCTs satisfied our eligibility criteria and were included in the present work for a total of 413 subjects with several cancer types (breast, head and neck, esophageal, and thoracic/gastric cancers). While some studies demonstrated significant pain reduction and improved quality of life post-BoNT-A injections, outcomes across different cancer types were inconclusive. Additionally, several effects were observed in functioning, dysphagia, salivary outcomes, esophageal strictures, gastric emptying, and expansions. This review emphasizes the need for further standardized research to conclusively establish the efficacy of BoNT in comprehensive cancer pain management.